Managing Complexity For Creating Breakthrough Inventions: Focusing On Collaboration Teams And Prior Art - Mun, Hee Jin; Chung, Yerim (Journal of Applied Business Research, 2017)
Inventing processes are often greatly complex, resulting in the difficulty of creating breakthrough inventions. But the relationship between the complexity of inventing and the creation of breakthrough inventions and ways of dealing with the complexity of inventing have received little research attention. This study focuses on the effect of coupling, one of the causes of complex inventing, on the likelihood of creating breakthrough inventions and suggests two moderating factors: the size of collaboration teams and the oldness of prior art. Based on U.S. granted patents in optical disc technology domains applied during 1997–2001, the empirical results showed the negative effect of coupling on the likelihood of creating breakthrough patents and the weakening moderating effect of the number of inventors involved in generating patents.
Keywords: Complex Inventing; Breakthrough Invention; Collaboration